An investigation into breast support and sports bra use in female runners of the 2012 London Marathon - Brown, N.; White, J.; Brasher, A.; Scurr, J. (Journal of Sports Sciences, 2014)
Although it is acknowledged that appropriate breast support during exercise is important, no published literature has assessed breast support usage in a cohort of female marathon runners. This study aimed to identify sport bra use and perceived importance of sports bra use in female marathon runners. Bra satisfaction, incidence of bra related issues and factors that influence the appropriateness of sports bras were also investigated. A 4-part, 30-question survey was administered to 1397 female runners at the 2012 London marathon registration and via an online survey. In total 1285 surveys were completed. Sports bra use and its perceived importance was high, however was lower in moderate compared to vigorous activity, and lower in participants with smaller breasts. Seventy-five per cent of participants reported bra fit issues. The most common issues were chaffing and shoulder straps digging in, with a higher incidence of issues reported by participants with larger breasts. Use of professional bra fitting was low, and perceived knowledge of breast health was poor. Engagement with sports bra use is high although sports bra design could be improved to alleviate bra fit issues experienced by female runners. Educational initiatives are needed to ensure females are informed regarding the importance of breast support and appropriate bra fit during activity.